Empathy in the Romantic Context: Design and Validation of a Measure - Sanchez Aragon, Rozzana (Pontificia Universidad Javeriana, 2016)
Empathy involves in its nature a series of other notions (Batson, 2009) whose highlights comprise two psychological elements in different degrees: cognition and emotion, which are linked each other. In one hand, empathy can be a kind of intellectual or imaginative comprehension about other without really experience the feeling of that person (i.e. Hogan, 1969), on the other hand, empathy is an emotional reaction or sympathy in response to the feelings or experiences of others (i.e. Mehrabian & Epstein, 1972). Due to its inherent interactional character of empathy, the couple relationship context becomes very interesting to explore; also because it includes a particular emotional and cognitive shades that favor the display of that variable which involve the integration of its members in a characteristic cognitive-emotional reading and thus determine the degree of intimacy and immediacy achieved by them. At this, the purpose of this research was to design and validate an empathy toward the partner measure in an intentional non probabilistic sample of 467 adults from Mexico City whose had a romantic relationship at the moment of the study. Findings show the extraction of four key factors in the understanding of empathy: perspective taking, cognitive empathy of emotions, self-disturbance and empathetic compassion. Those factors showed construct validity and moderate Cronbach reliability coefficients and they represent a conceptual, methodological and cultural contribution to the variable in the romantic context.